(untitled) (South East Asia Journal of Public Health, 2018)
Aripiprazole is drug that acts as a partial agonist at D2 and 5-HT1A receptors and antagonist at 5-HT2A receptor. It modulates the neurotransmission over activity on the dopaminergic mesolimbic pathway which is responsible for positive symptoms of Schizophrenia. Dopamine antagonism is the mechanism of action of first generation antipsychotics. In this paper we discuss an interesting case in which Aripiprazole was effective in decreasing Prolactin levels which was elevated secondary to previous Fluphenazine use. South East Asia Journal of Public Health Vol.7(2) 2017: 40-42